Uncommon : simple principles for an extraordinary life - Divine, Mark. (New York St. Martin's Press, 2024)
From former Navy SEAL, entrepreneur, father, and New York Times bestselling author Mark Divine comes Uncommon- an inspirational book following Mark Divine's trademark warrior monk philosophy that will lead you to the summit of personal development. To be common is to be an everyday person. It's to do the things that you are expected to do, whether that's what your parents want for you, or your employer, or your spouse, et cetera. But if you want to be more than you are, more than you think you can be, then you need to recognize and learn from your mistakes to lead a life of excellence. As an elite Navy SEAL, entrepreneur, author, speaker, professor of leadership, and philanthropist, as well as the creator of SEALFIT, Kokoro Yoga, and Unbeatable Mind, Mark Divine uses years of wisdom, business development, martial arts, eastern philosophy and military experience to take you through life's most important principles for finding your pursuit of excellence--so that you or anyone with the proper motivation can become uncommon"
Keywords: Motivation, Conduct of life